Fiscal Expenditure and Education Quality in China: A Regional Heterogeneity Analysis (European Journal of Marketing and Economics, 2024)
This study analyzes the impact of fiscal expenditure on education quality across Chinese provinces, focusing on the regional heterogeneity of policy effectiveness. Utilizing panel data from 2008 to 2016 and applying a two-way fixed effects model, we identify a consistent and significant positive relationship between fiscal input—particularly education-specific spending—and provincial education outcomes. This association remains robust after controlling for economic growth, industrial structure, and demographic factors. To capture spatial variations, the dataset is disaggregated into eastern and non-eastern (western and central) regions. The heterogeneity analysis reveals that fiscal expenditure yields stronger improvements in education quality in non-eastern provinces, where government spending appears to be a more efficient and impactful tool for human capital development. In contrast, fiscal inputs in more economically advanced eastern regions have a limited marginal effect on educational outcomes, implying diminishing returns and the potential necessity for non-monetary or structural reforms. These findings underscore the importance of regionally tailored policy design in maximizing the returns on public investment in education and highlight fiscal policy as a strategic lever in addressing regional disparities in human development.
Keywords: Fiscal Expenditure, Education Quality, China, Regional Disparity, Panel Data, Policy Efficiency